Design of a lumbar support device to prevent musculoskeletal injuries in Costa Rican coffee workers - Jiménez-Ortega, Monserrath (2026)
This article presents a study conducted during the first academic semester of 2025 by students from the Costa Rica Institute of Technology in Cartago. The development of Nöku consists of an intelligent lumbar support device designed to reduce the risk of musculoskeletal injuries among coffee harvesters. This population performs long working hours carrying heavy baskets on irregular terrain, such as the mountainous areas of Cartago, which exposes them to lumbar disorders and physical fatigue during coffee harvesting activities. As part of the research process, interviews were conducted with the director of the Agribusiness program and a coffee farmer, both with experience in coffee harvesting. The methodology was structured into five stages, including problem identification through observation and interviews, ergonomic analysis, formal and functional definition with technological integration, prototype validation, and documentation of results. The device integrated sensors and a haptic alert system to monitor the carried load in real time; when the weight exceeded the established limit, the system activated the alert, encouraging immediate load reduction. In addition, the design incorporated adjustable straps and padded lumbar support, allowing for weight redistribution and comfort during harvesting. The design was validated with five coffee harvesters through physical prototype testing and with twelve users through an online survey, evaluating the aesthetics and user perception of the device. The results demonstrated improvements in ergonomics, comfort, and reduction of musculoskeletal injury risk, confirming its viability and potential as a support device for coffee harvesters.